PAVING BLOK K-200 UNTUK AREA PARKIR MOBIL RECYCLE LIMBAH PAVING LAMA - Yuono, Teguh; Hartanto, Tri; Nursetyo, Gatot; Alif Widiyanto, Al Ibra (Jurnal Teknik Sipil dan Arsitektur, 2025)
Students use private vehicles with the aim of making it easier to mobilize from their residence to the University Campus environment. This influences the intensity of motorists in the university area to be high, so quality road infrastructure is needed so that students can drive comfortably and safely. One way to develop quality road infrastructure is by installing paving blocks. Generally, apart from installation on university roads, paving blocks are installed on sidewalks, pedestrians, parking areas, even in hotel and factory areas. Apart from roads, parking areas also need to be planned using paving. The ease of installation and costs required are considered cheaper and meet the aesthetic aspect because they have various shapes, making the use of paving blocks increasingly popular. The use of paving blocks as road pavement and parking areas is also needed in the Tunas Pembangunan Surakarata University environment. The conventional method of making paving blocks is done using a block tool with a compaction load that affects the energy of the person doing the work. The materials used in making paving blocks are Portland Cement, sand (old/paving waste), and water. In this research, 6 samples were made, with a ratio of 1:3. After 14 days, a press test of the paving was carried out and it was discovered that the new paving (recycled) had a strength of more than K-200 , so it could be used for roads and parking in the UTP Surakarta campus area.. Keyword: recycle paving, pressure test, old paving, K-200, parking